History and developement of the plow and reaper - Clarke, Lee S. (My University, 1907)
Introduction: There is no branch of farm industry in which the improvement has been so marked during the last half century as that shown in the developement of the important farm implements. This improvement has come, largely with the increase in the demand for superior tools, as the progress of civilization has demanded more of the comforts and luxuries of life. However, there was a long period in American farming, as well as that of other countries, in which the hired man was looked upon favorably who had strong arms and sinewy muscles for the difficult manual labor by which practically everything was accomplished. This condition existed until soon after the beginning of the ninteenth century when the increasing population and demand for improvements, called for something better.
Citation: Clarke, Lee S. History and developement of the plow and reaper. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Plow; Reaper; Agricultural Tools; Modern Agriculture; Technological Progress; Theses